Climate and sex ratio variation in a viviparous lizard. (31st May 2017) - Cunningham, George D.; While, Geoffrey M.; Wapstra, Erik
Abstract : The extent to which key biological processes, such as sex determination, respond to environmental fluctuations is fundamental for assessing species' susceptibility to ongoing climate change. Few studies, however, address how climate affects offspring sex in the wild. We monitored two climatically distinct populations of the viviparous skink Niveoscincus ocellatus for 16 years, recording environmental temperatures, offspring sex and date of birth. We found strong population-specific effects of temperature on offspring sex, with female offspring more common in warm years at the lowland site but no effect at the highland site. In contrast, date of birth advanced similarly in response to temperature at both sites. These results suggest strong population-specific effects of temperature on offspring sex that are independent of climatic effects on other physiological processes. These results have significant implications for our understanding of the ecological and evolutionary consequences of variation in sex ratios under climate change.